Vitelline artery remnant: A rare cause of chronic abdominal pain in an adult (Indian Journal of Case Reports, 2020)
Vitelline vascular remnant is a rare clinical entity in adults. Usually, they cause intestinal obstruction, especially in children. In adults, it can cause chronic abdominal pain. We report the case of a 53-year-old man who presented with recurrent abdominal pain for the past 1 year. Contrast-enhanced computed tomography of the abdomen and colonoscopy was normal. Diagnostic laparoscopy revealed a single band-like structure between the distal ileal mesentery and anterior abdominal wall near the umbilicus. Band resection was done. These bands are the rare cause of chronic abdominal pain in adults and difficult to diagnose, preoperatively. In these cases, laparoscopy is an effective diagnostic as well as a therapeutic tool.